Comparison of Efficacy of Azithromycin Versus Ceftriaxone in Treatment of Enteric Fever - Bushra Mehreen, Sadia Jehanzeb, Hashmat Ullah Khan, Rabbia Shaheen, Sahar Iqbal, Saima Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Research was conducted at the Hayatabad Medical Complex in Peshawar to evaluate the relative effectiveness of azithromycin and ceftriaxone in the treatment of enteric fever. Methods: After the ethical approval from institute review board, this random controlled trial was conducted at Department of Pediatrics, Hayatabad Medical Complex, Peshawar, from 20 July, 2019 to 20 Jan, 2020. Each patient was randomly assigned to a treatment group through toss method in Group A and Group B. Patients in Group A received azithromycin (20 mg/kg/day; maximum, 1000 mg/day) and patients in Group B were administered with ceftriaxone (75 mg/kg/day; maximum, 2.5 g/day). Efficacy of both drugs was determined keeping in view complete resolution of symptoms of enteric fever within a week time. Results: The mean ± S. D of age of the participants in both groups were 5.38±1.95 and 5.74±1.84 years. The mean ± S. D of disease duration of the participants in both groups were 6.14±1.25 and 5.90±1.17 days. The mean ± S. D of time of defersevence of the participants in both groups were 2.38±0.57 and 4.66±0.716. In azithromycin group, 44 (88%) patients showed effective results while in the ceftriaxone group, 23 (46%) patients showed effective results. P Value = 0.000 Conclusion: Azithromycin could be a convenient and cheap alternative for the treatment of typhoid fever, especially in children in our local population. Keywords: Azithromycin, Ceftriaxone, Typhoid Fever